Use of a novel pressure distribution system for severely ill neonates: a clinical pilot study carried out by the PREPICare consortium - Anna-Barbara Schlüer; Adrian Yves Müller; Nicolas Philip Fromme; Martin Camenzind; Robert Riener; René Michel Rossi; Barbara Brotschi Aufdenblatten (BMC, 2023)
Abstract Background Pressure Injuries are not exclusively an adult phenomenon; various risk factors contribute to a high prevalence rate of 43% in the neonatal and pediatric intensive care population. Effective preventive measures in this population are limited. Methods We performed a pilot study to analyze the distribution and localization of support surface interface pressures in neonates in a pediatric intensive care unit (PICU). The hypothesis was that pressure redistribution by a novel air mattress would reduce pressure peaks in critical neonates. The measurements were conducted in a 27-bed level III PICU between November and December 2020. This included measuring pressure distribution and pressure peaks for five neonates positioned on either a state-of-the-art foam mattress or a new prototype air mattress. Results We confirmed that the pressure peaks were significantly reduced using the prototype air mattress, compared with the state-of-the-art foam mattress. The reduction of mean pressure values was 9-29%, while the reduction of the highest 10% of pressure values was 23-41%. Conclusions The journey to an effective, optimal, and approved product for severely ill neonates to reduce Pressure Injuries is challenging. However, a crucial step was completed by this pilot study with the first pressure measurements in a real-world setting and the successful realization of a decrease in pressure peaks obtained using a prototype air mattress.